Visions of an inclusive school - Preferred futures by special education teacher students - Nikula, Elina (Taylor & Francis, 2025)
This study explores the desired future images of an inclusive school. In its policy documents, Finland has been committed to goals of inclusive education for decades; however, there are still challenges in its implementation. By utilising futures workshops, our research explores the factors envisioned by special education teacher students regarding the desired future of an inclusive school. The factors form three dimensions: structural, social, and emotional. Additionally, certain factors were assessed to fit into more than one dimension, which results in four overlapping aspects of services, commitment, a meaningful school path, and the school's comprehensive role in the community. Our results emphasise the systemic nature of inclusion in education, which further reinforces the understanding of inclusion as a process.